72 Relationships Among Lifetime Feed Efficiency Traits in Growing Heifers, Mature Cows and Their Progeny. (7th May 2021) - Lancaster, Phillip A; Davis, Mike; Rutledge, Jack; Cundiff, Larry
Abstract: Uncertainty exists in relationships among feed efficiency traits in different production stages. The objective of this study was to evaluate the relationships among feed efficiency traits measured in various stages of production. Data were collected from 1953 through 1980 from dams (n = 160), and their progeny (n = 406). Individual feed intake was measured from 240 d of age through weaning of 3 rd calf for dams, and from weaning to slaughter for progeny. Body weight was measured at 28-d intervals until first parturition for heifers and slaughter for progeny, and cows were weighed at parturition and weaning each production cycle. Milk yield of dams was measured at 14-d intervals throughout lactation. Residual feed intake was computed as the residual from linear regression of daily DMI on metabolic mid-test body weight, average daily gain, and milk yield for dams only with year-diet-breed factor as a random effect using lmer function in R software. Pearson correlation coefficients were computed using corr.test function. Pearson correlations of RFI with DMI ranged from 0.58 to 0.74 and with feed:gain or feed:milk ranged from 0.24 to 0.67 within production stage. Heifer RFI was correlated with cow RFI during parity 1 (0.74), but not parity 2 (0.11) or 3 (-0.06). Heifer RFI was correlated with progeny 3 RFI (0.17), but not progeny 1 or 2 RFI. Cow RFI was weakly correlated among parities (0.25 to 0.36) whereas feed:milk was strongly correlated (0.56 to 0.70). Cow RFI was not correlated with progeny RFI of the same parity. In conclusion, RFI was poorly correlated across stage of production.